2012
DOI: 10.5367/te.2012.0157
|View full text |Cite
|
Sign up to set email alerts
|

Demand for the Quality Conservation of Venice, Italy, According to Different Nationalities

Abstract: This paper focuses on visitor demand for the quality conservation of Venice according to different nationalities. The vast majority of visitors to Venice are foreigners (both tourists and day-visitors) who come from all over the world. In this research they are mainly categorized as non-Italian Europeans or non-Europeans. A specific theoretical model, in which quality conservation is provided publicly and also privately through donations, is presented for nationals and for foreigners. The data are obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Customer satisfaction has, finally, been seen as an indicator of destination competitiveness and performance (Enright and Newton, 2004;Alegre and Garau, 2010;Munier and Camelis, 2013). As reported by Neal and Gursoy (2008), most satisfaction studies are based on expectation and perception models (Oliver, 1980), cognitive evaluation (Klaus, 1985;Chadee and Mattsson, 1996), congruity models (Sirgy, 1984), equity models (Oliver and Swan, 1989) and perceived overall performance (Fuchs and Weiermair, 2004;Thompson and Schofield, 2007). So far the issue of customer satisfaction, consumer expenditure and consequently firms' economic benefits remains only partially examined and Anderson (1996), Anderson et al (1994Anderson et al ( , 1997 and Anderson and Mittal (2000) can be considered the pioneers in studies related to the link between customer satisfaction and profitability.…”
Section: Customer Satisfaction and Expenditurementioning
confidence: 93%
See 3 more Smart Citations
“…Customer satisfaction has, finally, been seen as an indicator of destination competitiveness and performance (Enright and Newton, 2004;Alegre and Garau, 2010;Munier and Camelis, 2013). As reported by Neal and Gursoy (2008), most satisfaction studies are based on expectation and perception models (Oliver, 1980), cognitive evaluation (Klaus, 1985;Chadee and Mattsson, 1996), congruity models (Sirgy, 1984), equity models (Oliver and Swan, 1989) and perceived overall performance (Fuchs and Weiermair, 2004;Thompson and Schofield, 2007). So far the issue of customer satisfaction, consumer expenditure and consequently firms' economic benefits remains only partially examined and Anderson (1996), Anderson et al (1994Anderson et al ( , 1997 and Anderson and Mittal (2000) can be considered the pioneers in studies related to the link between customer satisfaction and profitability.…”
Section: Customer Satisfaction and Expenditurementioning
confidence: 93%
“…However, in that respect, it is important to note that loyalty might not be as important to destinations as it is for other businesses or services (Kozak and Rimmington, 2000). Although past studies (Oliver and Burke, 1999;Hui et al, 2007) have demonstrated that tourists' overall level of satisfaction with the destination influences the intention to revisit, the dis/satisfaction with various components of the holiday experience (pre-trip services, services at the destination, transit route services) leads to overall dis/satisfaction (Neal and Gursoy, 2008), influencing future intentions (Kozak and Rimmington, 2000). Furthermore, although loyal customers mean more customers in general, lower impact of price fluctuations and less cost for the firm in attracting new customers due to positive word of mouth, in an industry, like tourism, affected by fixed capacity, are loyal (repeat) customers more likely to spend more at the destination?…”
Section: Customer Satisfaction and Expenditurementioning
confidence: 99%
See 2 more Smart Citations